2016
DOI: 10.1128/jvi.00060-16
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient CRISPR/Cas9-Mediated Cloning and Functional Characterization of Gastric Cancer-Derived Epstein-Barr Virus Strains

Abstract: The Epstein-Barr virus (EBV) is etiologically linked to approximately 10% of gastric cancers, in which viral genomes are maintained as multicopy episomes. EBV-positive gastric cancer cells are incompetent for progeny virus production, making viral DNA cloning extremely difficult. Here we describe a highly efficient strategy for obtaining bacterial artificial chromosome (BAC) clones of EBV episomes by utilizing a CRISPR/Cas9-mediated strand break of the viral genome and subsequent homology-directed repair. EBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 38 publications
1
69
0
1
Order By: Relevance
“…We suppose the reason may be the formation of superhelix of circular donor plasmid, and thus difficult to be incised by CRISPR/Cas9. However, in the recent construction of an Epstein–Barr virus-BAC system, only a circular donor plasmid, rather than a linearized one, produced successful HR though without exact HR efficiency (Kanda et al, 2016). Another study in which the PRV genome was manipulated with CRISPR/Cas9 showed that HR failed when a linearized homologous repair donor plasmid was inserted into the PRV genome, but achieved a recombinant efficiency of almost 50% when a homology-independent DNA repair mechanism was used (Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suppose the reason may be the formation of superhelix of circular donor plasmid, and thus difficult to be incised by CRISPR/Cas9. However, in the recent construction of an Epstein–Barr virus-BAC system, only a circular donor plasmid, rather than a linearized one, produced successful HR though without exact HR efficiency (Kanda et al, 2016). Another study in which the PRV genome was manipulated with CRISPR/Cas9 showed that HR failed when a linearized homologous repair donor plasmid was inserted into the PRV genome, but achieved a recombinant efficiency of almost 50% when a homology-independent DNA repair mechanism was used (Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9 is emerging as a powerful tool for DNA engineering in diverse organisms, and allows efficient DNA editing (Cong et al, 2013). Gene knock-in of large DNA viruses with CRISPR/Cas9 has been reported, including of adenovirus (Bi et al, 2014), Herpes simplex virus 1 (Bi et al, 2014), PRV (Xu et al, 2015; Liang et al, 2016; Tang et al, 2016), and Epstein–Barr virus (Kanda et al, 2016). However, there is little information about the features of CRISPR/Cas9 that are important in enhancing the efficiency of the HR between PRV and BAC.…”
Section: Introductionmentioning
confidence: 99%
“…EBV genome shows heterogeneity during the progression of infection that generates new pathogenic strains which reduces the effects of antiviral drugs . Kanda et al used CRISPR/Cas9‐mediated cloning of disease‐associated viral strains in gastric cancer cell lines. A plasmid pX330‐sgEBV was constructed to cleave a target site of BVRF1 ORF and triggers the insertion of 12 kb transgenes into the EBV genome via homology‐directed repair.…”
Section: Implication Of Crispr/cas9 In Combating Oncovirusesmentioning
confidence: 99%
“…Recently, it has been shown that CRISPR/Cas9-mediated cleavage for bacterial artificial chromosome (BAC) insertion into EBV episomal DNA in gastric carcinoma (GC) cell lines has facilitated the cloning of these viral genomes with unprecedented efficiency 41 . Subsequent infection of epithelial cells with the BAC clone reconstituted viruses induced resistance to oncogene-induced cell death, providing important clues concerning EBV-mediated epithelial carcinogenesis.…”
Section: Epstein-barr Virus Infection In Gastric Cancermentioning
confidence: 99%